Inflammation disrupts epithelial barrier function and induces the release of different populations of exosomes. (24th June 2020) - Martins, B; Rodrigues, T; Ramalho, J; Ambrósio, A; Girão, H; Fernandes, R
Abstract: Introduction Age-related macular degeneration (AMD) is a degenerative retinal disease that affects central vision. Most of their phenotypical features are believed to be associated with the dysfunction of retinal pigment epithelium (RPE). The accumulation of damaged proteins in aged RPE is associated with disruption of proteolytic pathways and exocytic activity, with release of intracellular proteins via exosomes (Exo), that are important players in intercellular communication and can contribute to disease progression. However, the impact of their secretion by polarized RPE on outer blood retinal barrier (oBRB) breakdown remains largely elusive Objectives Our aim was to explore the role of inflammation on the loss of RPE integrity and to understand the relative role of directional secretion of Exo by RPE in the loss of polarity and barrier disruption Methodology We used a human RPE cell line (ARPE-19), highly polarized RPE primary cultures (pRPE) and porcine eyecups. To mimic the inflammatory conditions present in AMD, cells were treated with two inflammatory stimuli, TNF (10 ng/mL) or LPS (100 ng/mL) Results TNF and LPS do not affect the viability of the RPE cells. RPE cells developed a confluent monolayer and reached a relatively constant TER of about 40 Ω/cm2 (ARPE-19) or higher than 150 Ω/cm2 (pRPE). Treatment with TNF significantly reduces the TER, decreased immunoreactivity and co-localization of the TJ proteins ZO-1 and occludin and increases MMP-2/-9 activity in the medium. Apical Exo isolated from the RPE cells are enriched in CD63 compared to the basolateral Exo, that are enriched in CD81. The Exo isolated from porcine eyecups, especially with the LPS stimulus, are enriched in CD81 and MMP-2 but have similar levels of CD63 Conclusion Overall, our results show that inflammation induces loss of RPE integrity and release of different populations of Exo. The unravelling of novel drug targets paves the way for development of new therapeutic strategies for AMD.